Technical Electrosmog May be Dangerous (Global Journal of Medical Research, 2023)
It is scientifically controversial so far whether EMF non-ionizing electromagnetic fields can have negative effects on the DNA of cell nuclei In terms of their energy they could not do so However there is clinical and molecular biological evidence that this can be There exists a 3- stage mechanism of action via peroxinitrite which could lead to DNA damage The sequence of these processes will be described Therefore there is a reasonable suspicion that EMF could also cause DNA damage The organs with fast and high cell division rate are particularly affected The general exposure to technical electrosmog especially 5G must therefore be marked with a question mark
Keywords: technical electromog; electro-magnetic fields - EMF; DNA damages; 5G